The Emergence of New Infectious Diseases Is a Global Problem for Humanity - Baykhanova N.T. (Academia One, 2024)
On the threshold of the 21st century, humanity has come to realize the importance of global tasks of ensuring the safety of people's lives. These tasks, among security issues, have become among the most important priorities of the countries of the world, as well as the international community. The most urgent need to solve these problems has manifested itself in connection with the challenges and threats that have arisen in the demographic, environmental, political, and social spheres of human life. The mentioned challenges and threats were the most striking signs of the systemic crisis of civilization.
Keywords: infectious; mortality; epidemic; prevention